On Intentionality and Figurative Language Comprehension - Harutyunyan, Gohar (Armenian Folia Anglistika, 2007)
The communicative intent which is a linguo-philosophical notion is important from the perspective of pragmatic analysis. The article attempts to examine the complicated interconnection between the intention of communication and the perception of the figurative language. Special attention has been paid to metaphor and irony whose perception and interpretation heavily depend on the intention of communication.